The Effect of Using POE-Based Worksheet on Student’s Learning Outcomes in Material of Impulses and Momentum - Dwi Kusdayanti; I Dewa Putu Nyeneng; Nengah Maharta (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
This study aims to determine the effect of using POE-based worksheets on student’s learning outcomes of physics in the material of impulses and momentum at SMAN 5 Bandar Lampung. The research population was all students of class X MIA. The design of this study uses True Experimental Design with a Pretest-Posttest Control Group Design type. The research sample in this study was class X MIA1 and X MIA2 with relatively similar initial abilities so that the Simple Purposive Sampling technique was used. The independent sample t-test results showed a significance value of 0,000 for cognitive, psychomotor learning outcomes through questions and through practical performance so that the use of POE-based worksheets on impulses and momentum material had a significant effect on student learning outcomes. The magnitude of the effect obtained from the results of the effect size test (Cohen d) is 2,18 for the cognitive domain; 1,34 and 1,21 for the psychomotor domain (high category). This means that the use of POE-based worksheet in this study has a large effect on student learning outcomes.